Phytochemistry and antidiabetic activity of derris elliptica methanolic leaves extract / Rassheda Abd Rahman - Abd Rahman, Rassheda (2020)
Derris elliptica is a medicinal plant from the Fabaceae family, a species of leguminous plant and this plant locally known as 'akar tuba'. This study aims to investigate the phytochemical constituents and also anti-diabetic activity of Derris elliptica methanolic leaves extract (DEME) on streptozocin (STZ) induced diabetic sprague dawley rats. Maceration technique and chromatographic technique were performed for extraction and identification of phytoconstituents respectively. Fractions from column chromatography were observed by Thin layer chromatography (TLC) with various solvents systems. Acute oral toxicity studies were assessed by 2 g/kg body weight (bwt) in normal rats.